Perbandingan Hasil Belajar Peserta Didik Kelas X SMA Negeri 1 Ma’rang yang Diajar melalui Model Pembelajaran Kooperatif Tipe TPS dan NHT (Studi Pada Materi Pokok Ikatan Kimia) - Sugiarti, Sugiarti; Danial, Muhammad (Jurusan Kimia FMIPA UNM, 2021)
This study is a comparison research with quasi-experimental method aimed to investigate the differences of learning outcomes of student Class X SMA Negeri 1 Ma’rang between taught using of TPS and NHT types of cooperative learning. The study design was